2020
DOI: 10.21037/atm-20-2372
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of the neutrophil-to-lymphocyte ratio and CRP to predict 7-day disease severity in 84 hospitalized patients with COVID-19 pneumonia: a retrospective cohort study

Abstract: Background: Coronavirus disease 2019 (COVID-19) has spread rapidly worldwide from Wuhan. An easy-to-use index capable of the early identification of inpatients who are at risk of becoming critically ill is urgently needed in clinical practice. Hence, the aim of this study was to explore an easy-to-use nomogram and a model to triage patients into risk categories to determine the likelihood of developing a critical illness. Methods: A retrospective cohort study was conducted. We extracted data from 84 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 23 publications
6
70
0
Order By: Relevance
“…In this study, there is a trend that patients with good outcomes have lower NLR, CRP, and serum ferritin compared to patients who died or remained critically ill. NLR has been shown to have a good predictive value in assessing patients who are likely to have severe SARS-CoV2 infection (30,(93)(94)(95)(96). In particular, it has been proposed that patients who are older and have NLR values of more than 3 are likely to require intensive care (27).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there is a trend that patients with good outcomes have lower NLR, CRP, and serum ferritin compared to patients who died or remained critically ill. NLR has been shown to have a good predictive value in assessing patients who are likely to have severe SARS-CoV2 infection (30,(93)(94)(95)(96). In particular, it has been proposed that patients who are older and have NLR values of more than 3 are likely to require intensive care (27).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 42 studies were further scrutinized by reading the full text. Finally, only 19 studies were included in this meta-analysis, of which 9 reported the predictive value on disease severity [26][27][28][29][30][31][32][33][34], 6 reported the predictive value on mortality [35][36][37][38][39][40], and 4 reported the predictive value on both disease severity and mortality [41][42][43][44].…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…By 26 June 2020, COVID-19 had affected 213 countries, with over 9,621,470 confirmed cases and 487,295 deaths worldwide (COVID-19 CoV—Update , accessed 26 June 2020). The least absolute shrinkage and selection operator (LASSO) regression has been used to identify the important factors of severity transition in COVID-19 patients ( Liu et al, 2020 ), and critically ill patients exhibited respiratory failure, acute respiratory distress syndrome, heart failure, and septic shock, which increased the mortality of COVID-19 patients ( Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%